The Influence of Knowledge Level and Family Support on Medication Adherence in Tuberculosis Patients: Pengaruh Tingkat Pengetahuan dan Dukungan Keluarga terhadap Kepatuhan Minum Obat pada Pasien Tuberkulosis - Susila, Arif; Tasbihul Anwar; Agus Sustiyono; Fitri Setiawati (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction; Tuberculosis (TB) remains a significant public health issue both in Indonesia and globally, caused by the bacteria Mycobacterium tuberculosis. Knowledge and the role of the family are crucial factors influencing an individual's adherence to medication. Understanding these factors is essential for designing effective interventions to improve treatment compliance among TB patients. Objectives; The objective of this study is to determine the relationship between the level of knowledge and the role of the family with medication adherence in TB patients within the working area of the Ciruas Health Center, Serang Regency, in 2024. Methods; This study employed a quantitative correlational design using a cross-sectional approach. The population consisted of 210 TB patients undergoing treatment at the Ciruas Community Health Center in 2023. Purposive sampling was used to select participants. Data collection utilized validated questionnaires on knowledge, family roles, and medication adherence. Statistical analysis was performed using the Chi-Square test with a significance level of <0.05. Results; The Chi-Square test revealed a significant relationship between the level of knowledge and medication adherence among TB patients (p=0.000). Additionally, a significant relationship was found between the role of the family and medication adherence (p=0.000). The analysis categorized the patients' level of knowledge as moderate, family roles as poor, and medication adherence as moderate. Conclusions; The study highlights that both knowledge and family support play a vital role in influencing medication adherence among TB patients. These findings emphasize the need for educational interventions and family-centered strategies to enhance compliance with TB treatment regimens. Implementing these measures could contribute to better treatment outcomes and a reduction in TB incidence